KONSEPTUALISASI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS ICT DENGAN PENDEKATAN GAME-BASED LEARNING MELALUI QUIZIZZ UNTUK MENDUKUNG PENINGKATAN HASIL BELAJAR SISWA. - Nailul Muna; Nurmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information and communication technology (ICT) has brought significant changes to the world of education, including in Islamic Religious Education (PAI). This study aims to identify and analyze the concept of ICT-based Islamic Religious Education (PAI) learning using a Game-Based Learning approach through the Quizizz application and to describe its impact on student learning outcomes. Problems identified in the field indicate that PAI learning is still dominated by lecture methods, low student engagement in the learning process, and the suboptimal use of technology as a learning medium. This study employed a qualitative descriptive method with data collection techniques including interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the use of Quizizz as an ICT-based learning medium can increase student motivation, active participation, and understanding of the learning material. The integration of game elements through Game-Based Learning provides a more engaging learning experience, thus positively impacting student learning outcomes. The research findings yield an ICT-based PAI learning concept that combines digital technology, interactive learning activities, and game-based evaluation to enhance learning effectiveness.